1998
DOI: 10.1159/000025570
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-Induced Collagen Synthesis in Cultured Smooth Muscle Cells from Rabbit Aortic Media and a Possible Involvement of Angiotensin II and Transforming Growth Factor-β

Abstract: Mechanical strain reportedly stimulates the synthesis of collagen in vascular smooth muscle cells (SMCs). The present study was designed to investigate a possible involvement of angiotensin II (Ang II) and transforming growth factor (TGF)-β in stretch-induced collagen synthesis of cultured SMCs derived from the rabbit aortic media. SMCs were cyclically stretched at a rate of 10% elongation and 30 cycles/min for 24 h using the Flexercell® strain unit (Flexcell International Corp., McKeesport, Pa.). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(113 citation statements)
references
References 41 publications
7
103
1
2
Order By: Relevance
“…Effects of Cyclic Stretch on Ang II Secretion into Culture Medium-A previous study using the Flexercell strain system showed that concentration of immunoreactive Ang II in the conditioned medium was elevated by cyclic stretch of VSMCs (12), and in the present study cyclic stretch of VSMCs caused increases in ACE and AT1 receptor mRNA expression. To determine whether the autocrine/paracrine-secreted Ang II actually contributes to the increase in FN mRNA expression in response to cyclic stretch, incubation medium obtained from VSMCs that were stretched for 12 h was transferred to VSMCs cultured on regular culture dishes.…”
Section: Effects Of Transcriptional Inhibitor and Protein Synthesissupporting
confidence: 66%
See 2 more Smart Citations
“…Effects of Cyclic Stretch on Ang II Secretion into Culture Medium-A previous study using the Flexercell strain system showed that concentration of immunoreactive Ang II in the conditioned medium was elevated by cyclic stretch of VSMCs (12), and in the present study cyclic stretch of VSMCs caused increases in ACE and AT1 receptor mRNA expression. To determine whether the autocrine/paracrine-secreted Ang II actually contributes to the increase in FN mRNA expression in response to cyclic stretch, incubation medium obtained from VSMCs that were stretched for 12 h was transferred to VSMCs cultured on regular culture dishes.…”
Section: Effects Of Transcriptional Inhibitor and Protein Synthesissupporting
confidence: 66%
“…This process allows cell culture in a uniform mechanically active environment so that all cells stretched over the loading station surface receive the same amount of strain. Previous studies showed that cyclic stretch of VSMCs with the Flexercell Strain Unit induced increases in DNA synthesis and total protein synthesis, thereby suggesting that this system is useful for in vitro analysis of the processes involved in vascular remodeling (11,12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The device consisted of a computer-controlled vacuum unit, a culture well plate with a flexiblepolystyrene culture well bottom coated with type I collagen (Flex I, Flexercell International Corp., McKeesport, PA, USA), and another culture well plate with a non-deformable culture well bottom made of the same materials as Flex I (Flex 11, Flexercell International Corp., McKeesport, PA, USA). Application of a vacuum provides a hemispherically downward deformation to the flexible Flex I bottom, resulting in a non-homogenous strain profile with a maximum at the Table 2 Sequences of RT-PCR primers used in the present study periphery and a geometric decline toward zero at the center or the culture well bottom [2,4,9,19,21]. The cells were placed in Flex I and Flex I1 culture well plates at a density of 1 x 10' cellslwell.…”
Section: Methodsmentioning
confidence: 99%
“…Smooth muscle cells, which are contained in the middle layer of an artery, are important constituents of the vascular system and they are responsible for control of short-term changes in lumen diameter and of long-term changes in the extracellular matrix turnover (e.g. Li et al 1998). In this section we provide an overview of the relevant continuum modelling aspects.…”
Section: Active Response Of Artery Wallsmentioning
confidence: 99%